The Role of Oxidative Stress and Cellular Senescence in the Pathogenesis of Metabolic Associated Fatty Liver Disease and Related Hepatocellular Carcinoma - Nikolaos-Andreas Anastasopoulos; Antonia V. Charchanti; Alexandra Barbouti; Eleftheria M. Mastoridou; Anna C. Goussia; Anastasia D. Karampa; Dimitrios Christodoulou; Georgios K. Glantzounis (MDPI AG, 2023)
Hepatocellular carcinoma (HCC) represents a worryingly increasing cause of malignancy-related mortality, while Metabolic Associated Fatty Liver Disease (MAFLD) is going to become its most common cause in the next decade. Understanding the complex underlying pathophysiology of MAFLD-related HCC can provide opportunities for successful targeted therapies. Of particular interest in this sequela of hepatopathology is cellular senescence, a complex process characterised by cellular cycle arrest initiated by a variety of endogenous and exogenous cell stressors. A key biological process in establishing and maintaining senescence is oxidative stress, which is present in multiple cellular compartments of steatotic hepatocytes. Oxidative stress-induced cellular senescence can change hepatocyte function and metabolism, and alter, in a paracrine manner, the hepatic microenvironment, enabling disease progression from simple steatosis to inflammation and fibrosis, as well as HCC. The duration of senescence and the cell types it affects can tilt the scale from a tumour-protective self-restricting phenotype to the creator of an oncogenic hepatic milieu. A deeper understanding of the mechanism of the disease can guide the selection of the most appropriate senotherapeutic agent, as well as the optimal timing and cell type targeting for effectively combating HCC.